Impact of different front-of-pack nutrition labels on online food choices - Santos, O (2020)
Front-of-pack nutrition labels (FOP-NL) are efficient tools for increasing consumers' awareness of the nutritional quality of food products, prompting healthier food choices. The main goal of this study was to evaluate the impact of four FOP-NL schemes - Traffic Light label (TL), Guideline Daily Amounts (%GDA), Nutri-Score (NS) and Health Star Rating (HSR) - on consumers' selection of food products according to perceived nutritional quality. A cross-sectional open-label crossover randomized controlled study was carried out among Portuguese consumers. A web-based questionnaire was used to assess participants' a) preferences regarding FOP-NLs and b) capacity to select healthy products in a food selection task using the information from FOP-NL schemes. When performing the selection task, participants had the option to indicate that they could not decide simply based on the presented FOP-NL (requiring more information). Overall, 357 adults participated in the study. Regarding consumers' preferences, TL received the most favorable responses, while NS received the fewest. All FOP-NLs performed better than the no-nutritional label control condition in the food selection task. The highest proportion of correct choices was obtained for TL (72.3%), followed by HSR (70.9%), %GDA (70.0%) and NS (62.2%), though no significant differences were found among FOP-NLs. Percentages of respondents indicating not being able to answer due to lack of information affected the proportion of correct choices, with 10.3% for TL, 12.9% for %GDA, 14.6% for HSR, and 25.8% for NS, indicating they were unable to choose without additional information. Although no particular FOP-NL system stood out as the most significantly effective, TL was the most preferred by Portuguese adults. Long-term real-world evidence is necessary to assess the impact of FOP-NL systems on individuals' food choices.